Combating anonymous offenders in the cyberspace: An overview of the legal approach in Malaysia - Nazli, Ismail@Nawang (2017)
Among the most treasured characteristics of the Internet is arguably its default technical architecture that facilitates online anonymity. This feature is most commonly cherished by Internet users as they are empowered to publish online content anonymously; or in the alternative to conceal their true identities behind fictitious names (pseudonyms). Anonymity is believed to have bolstered freedom of speech as any speakers could freely express their ideas or personal views in the cyber world without the fear of being identified and retaliated. Unfortunately, anonymity poses new challenges to law enforcement agencies as well as victims of cyber-crimes as they would find it difficult to trace and identify the culprits. For that reason, the Malaysian legislature has in 2012 passed a new law, section 114A of the Evidence Act 1950 that has the effect of shifting the burden of proof on the alleged offenders to prove his innocence. The passing of this controversial provision has led to heated debates between the government and human right defenders on the ground that such law seems to be very oppressive and could be easily manipulated by prosecutors in criminal cases as well as claimants in civil suits. By referring to reported cases and judicial decisions, this paper attempts to scrutinize in details section 114A of the Evidence Act 1950 and its implications on the legal system in the country; and ultimately to lend some assistance in unravelling the dispute between the proponents and opponents of the new law.